High-Throughput Screening of Human Leukemia Xenografts to Identify Dexamethasone Sensitizers. (December 2014) - Toscan, Cara E.; Failes, Tim; Arndt, Greg M.; Lock, Richard B.
Acute lymphoblastic leukemia (ALL) is the most common pediatric malignancy. Glucocorticoids (e.g., dexamethasone) form a critical component of chemotherapy regimens for pediatric ALL, and the initial response to glucocorticoid therapy is a major prognostic factor, where resistance is predictive of poor outcome. We have previously established a clinically relevant ALL xenograft model, consisting of primary pediatric ALL biopsies engrafted into immune-deficient mice, in which in vitro and in vivo dexamethasone sensitivity significantly correlated with patient outcome. In this study, we used high-throughput screening (HTS) to identify novel compounds that reverse dexamethasone resistance in a xenograft (ALL-19) derived from a chemoresistant pediatric ALL patient that is representative of the most common pediatric ALL subtype (B-cell precursor [BCP-ALL]). The compound 2-(4-chlorophenoxy)-2-methyl- N -(2-(piperidin-1-yl)phenyl)propanamide showed little cytotoxic activity alone (IC50 = 31 µM), but when combined with dexamethasone, it caused a marked decrease in cell viability. Fixed-ratio combination assays were performed against a broad panel of dexamethasone-resistant and -sensitive xenografts representative of BCP-ALL, T-cell ALL, and Mixed Lineage Leukemia– rearranged ALL, and synergy was observed in six of seven xenografts. We describe here the development of a novel 384-well cell-based high-throughput screening assay for identifying potential dexamethasone sensitizers using a clinically relevant ALL xenograft model.